2018
DOI: 10.1038/s41550-017-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric reconnaissance of the habitable-zone Earth-sized planets orbiting TRAPPIST-1

Abstract: Seven temperate Earth-sized exoplanets readily amenable for atmospheric studies transit the nearby ultra-cool dwarf star TRAPPIST-1 1, 2 . Their atmospheric regime is unknown and could range from extended primordial hydrogen-dominated to depleted atmospheres 3-6 .Hydrogen in particular is a powerful greenhouse gas that may prevent the habitability of inner planets while enabling the habitability of outer ones [6][7][8] . An atmosphere largely dominated by hydrogen, if cloud-free, should yield prominent spectro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
204
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(217 citation statements)
references
References 35 publications
13
204
0
Order By: Relevance
“…Although methods exist to correct the WFC3 first-orbit systematics (e.g. Zhou et al 2017;de Wit et al 2018), we opted for this approach to be consistent with our previous analyses (Evans et al 2016(Evans et al , 2017 and to avoid modeling the baseline trend over the full fiveorbit visits, which is less likely to be well approximated as linear. The resulting four-orbit white light curves were fit using a similar methodology to that described in Evans et al (2017), in which the systematics are treated as a Gaussian process (GP).…”
Section: White Light Curve Analysesmentioning
confidence: 99%
“…Although methods exist to correct the WFC3 first-orbit systematics (e.g. Zhou et al 2017;de Wit et al 2018), we opted for this approach to be consistent with our previous analyses (Evans et al 2016(Evans et al , 2017 and to avoid modeling the baseline trend over the full fiveorbit visits, which is less likely to be well approximated as linear. The resulting four-orbit white light curves were fit using a similar methodology to that described in Evans et al (2017), in which the systematics are treated as a Gaussian process (GP).…”
Section: White Light Curve Analysesmentioning
confidence: 99%
“…The combined spectrum of the planets rules out cloud-free, hydrogen-dominated atmospheres, except for TRAPPIST-1 f and 1 g (de Wit et al 2018;Moran et al 2018); Wakeford et al (2019) recently suggested that a clear hydrogen-dominated atmosphere may be ruled out for TRAPPIST-1 g. Since high-altitude clouds and haze are not expected to form in hydrogen-dominated atmospheres around temperate planets (e.g. Morley et al 2015), transit spectroscopy of the TRAPPIST-1 planets suggests no atmosphere or a high-metallicity atmosphere referred to as a secondary atmosphere.…”
Section: Introductionmentioning
confidence: 95%
“…Hubble Space Telescope (HST)/Wide Field Camera 3 (WFC3) measurements exhibit no prominent absorption features at near-infrared wavelengths in transmission spectra of six of the TRAPPIST-1 planets (de Wit et al 2016(de Wit et al , 2018Zhang et al 2018;Burdanov et al 2019)…”
Section: Introductionmentioning
confidence: 99%
“…Orbiting small stars, these planets provide an accelerated path toward finding and characterizing potentially habitable worlds. The TRAPPIST-1 planets already have transmission spectra measured by Hubble (de Wit et al 2018;Zhang et al 2018). With >7 times more collecting area and infrared instruments, the James Webb Space Telescope (JWST) will be capable of providing a more detailed look into the atmosphere of these cold exoplanets (Beichman et al 2014).…”
Section: Introductionmentioning
confidence: 99%